Simulation-Based Sailboat Trajectory Optimization using On-Board Heterogeneous Computers - Dębski, Roman (Computer Science, 2017)
A dynamic programming-based algorithm adapted to on-board heterogeneouscomputers for simulation-based trajectory optimization was studied inthe context of high-performance sailing. The algorithm can efficiently utilizeall OpenCL-capable devices, starting the computation (if necessary, in singleprecision)on a GPU and finalizing it (if necessary, in double-precision) withthe use of a CPU. The serial and parallel versions of the algorithm are presentedin detail. Possible extensions of the basic algorithm are also described. Theexperimental results show that contemporary heterogeneous on-board/mobilecomputers can be treated as micro HPC platforms. They offer high performance(the OpenCL-capable GPU was found to accelerate the optimization routine 41fold) while remaining energy and cost efficient. The simulation-based approachhas the potential to give very accurate results, as the mathematical model uponwhich the simulator is based may be as complex as required. The black-box representedperformance measure and the use of OpenCL make the presentedapproach applicable to many trajectory optimization problems.